2011
DOI: 10.1186/gb-2011-12-2-r18
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and minimizing PCR amplification bias in Illumina sequencing libraries

Abstract: Despite the ever-increasing output of Illumina sequencing data, loci with extreme base compositions are often under-represented or absent. To evaluate sources of base-composition bias, we traced genomic sequences ranging from 6% to 90% GC through the process by quantitative PCR. We identified PCR during library preparation as a principal source of bias and optimized the conditions. Our improved protocol significantly reduces amplification bias and minimizes the previously severe effects of PCR instrument and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
907
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,032 publications
(933 citation statements)
references
References 22 publications
19
907
2
5
Order By: Relevance
“…The level 2 metric is a measure of which exons failed to achieve 50Â unique coverage at 95% of exonic positions; this is frequently the first exon of genes, which are often GCrich and therefore difficult to amplify by PCR and/or to capture by fluid-phase targeted hybrid capture. 51 Of the 14 exons that failed this level of QC on an average validation run, 2 exons are entirely noncoding; according to the COS-MIC database, no recurrent mutations are reported in the remaining 12 exons. It is unlikely, therefore, that a clinically important mutation would be missed because of the lower coverage in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…The level 2 metric is a measure of which exons failed to achieve 50Â unique coverage at 95% of exonic positions; this is frequently the first exon of genes, which are often GCrich and therefore difficult to amplify by PCR and/or to capture by fluid-phase targeted hybrid capture. 51 Of the 14 exons that failed this level of QC on an average validation run, 2 exons are entirely noncoding; according to the COS-MIC database, no recurrent mutations are reported in the remaining 12 exons. It is unlikely, therefore, that a clinically important mutation would be missed because of the lower coverage in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has shown that amplification-free protocols can reduce the bias [which type of bias?] originated from PCR amplification 32,33 . Sequencing coverage of the transcriptome from these protocols is more even and contiguous across transcripts, making it easier to construct full-length transcripts.…”
Section: Library Constructionmentioning
confidence: 99%
“…88 Other than affecting fragmentation, GC content has a relevant impact on cDNA amplification efficiency. 91 GC-rich RNA fragments undergo base pairing and often form double-strand or highly-paired secondary structures that affect -or impede -reverse transcription of such fragments, leading to a dramatic unbalance in PCR products. 90 Furthermore, RNA-to-cDNA conversion (retrotranscription) before sequencing may introduce biases and artifacts interfering with the characterization and quantification of transcripts.…”
Section: Rna-seq In Human Complex Diseasesmentioning
confidence: 99%
“…Other effects, such as the choice of PCR enzyme or instruments have been also raised, and RNA-Seq in human complex diseases V Costa et al globally the PCR amplification has been identified as the most discriminatory step with some relevant hidden factors still to be examined. 91 To overcome the previously cited limitations of RT and amplification, direct single molecule RNA sequencing approach has been developed, 92 in which PCR amplification is no more required. However, the higher error rate compared with other reversible terminator chemistries is a severe issue even for this technology (discussed in Metzker et al 93 ).…”
Section: Rna-seq In Human Complex Diseasesmentioning
confidence: 99%